TINGKAT KEPUASAN DAN ASUPAN ZAT GIZI MAKRO DENGAN STATUS GIZI REMAJA PUTRI - Wahyuni Sulistiawati; Rudy Hartono; Thresia Dewi Kartini B (Politeknik Kesehatan Makassar, 2017)
Health Polytechnic Islamic boarding school is one of the institutions that serve the food needs of students, so they must have a good food management system. Food is said to be nutritious if it contains enough nutrients to meet the body's needs. This study aims to determine the relationship between the level of satisfaction and intake of macro nutrients with the nutritional status of young women in the Nahdlatul Ulum Islamic boarding school Maros. This research is an analytical research. The samples were 95 junior high school girls of class VII and VIII who were selected by purposive sampling. The level of satisfaction was obtained using a manually processed questionnaire using scoring. Intake of macro nutrients is obtained through non-consecutive 2x24 hours recall and then processed using nutrient 2008 and compared with AKG. Nutritional status is obtained through anthropometric measurements. The relationship between the variable level of satisfaction and intake of macro nutrients with nutritional status was done by Chi Square test. Data is presented using frequency tables and narratives. The results showed that the sample who liked rice dishes were 67 people (70.5%), animal side dishes 70 people (73.7%), vegetable side dishes 67 people (70.5%), vegetables 70 people (73.7%), and the level of satisfaction in food was 85 people (89.5%). Samples that had good protein intake of 95 people (100%), good fat intake of 49 people (51.6%) and less carbohydrate intake of 79 people (83.2%). Nutritional status of 49 people (51.6%) is normal based on BMI / U. The results of statistical tests concluded that there was no significant relationship between the level of satisfaction and intake of macro nutrients with the nutritional status of young women in the Nahdlatul Ulum Islamic Boarding School Maros. Keywords: Intake of Macro Nutrition, Nutritional Status, Adolescent, Satisfaction Level.